Abnormal precipitation of the μ phase during solution treatment of γ′-strengthened Co-Ni-Al-W-based superalloys. (May 2020) - Zhou, Xiaozhou; Fu, Huadong; Xue, Fei; Zhang, Yi; Xie, Jianxin
Abstract: Generally, μ phase preferentially precipitates at the place where the refractory elements segregate. However, in this study, the μ phase preferentially formed in the interdendritic regions of Co-Ni-Al-W-based superalloys during solution treatment, while the refractory elements W and Cr segregate to the dendritic cores. The microstructure evolution of the alloy during solution treatment was investigated. It showed that three different mechanisms caused this abnormal precipitation in the interdendritic regions, including primary carbides degeneration, further degeneration of the secondary carbides formed by the Laves phase decomposition, and direct precipitation from the interdendritic regions induced by the Laves phase decomposition. Graphical abstract: Image, graphical abstract